Analysing the Effectiveness of an Online Campaign’s Messages - Siti Khadijah; Nada Muthiah Shabirah (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2025)
Depressions among women, especially young women can happen due to the lack of support systems around them. Thus, it is important to create a support system where women can thrive from the support given to them. In this regard, Rahasia Gadis, an online community developed aims to provide a support system for women, especially young ones. This research analyzed the effectiveness of messages given in the #DariGadisKeGadis, an online campaign created by Rahasia Gadis to the participants’ eagerness to create a support system for people, especially young women around them. This research used a descriptive quantitative research design. This research applied a convenience sampling technique to obtain the participants. The results of this research indicate the positive impacts of the #DariGadisKeGadis campaign’s messages to the participants' willingness to develop a support system.